The INFLUENCE OF ENVIRONMENTAL PERFORMANCE, MANAGEMENT OWNERSHIP AND COMPANY CHARACTERISTICS ON ENVIRONMENTAL DISCLOSURE - Mafira Gita Apriliani; Ahmad Rifa’i (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The objective of this study is to find empirical evidence about the effect of environmental performance, managerial ownership, and company characteristics on environmental disclosure and its implications for firm value. The research sample is 50 public companies listed on the Indonesia Stock Exchange for the 2016-2018 period. The data analysis technique used is partial least square analysis. The results of this study indicate that environmental performance, managerial ownership, and company characteristics have an effect on environmental disclosure. The results of the study can be taken into consideration for companies to improve the quality of financial reporting to provide financial and non-financial information to stakeholders for the decision making process. In addition, the regulator can also use the results of this study as consideration for making regulations regarding adequate voluntary disclosure. Keywords: Environmental performance, Managerial ownership,Company size, Industry Tipe, Profitability environmental disclosure